Corporate Social Responsibility dan Free Cash Flow pada Tax Avoidance - Dewi, Ni Putu Sintia Sukma; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 31 No 5 (2021)DO - 10.24843/EJA.2021.v31.i05.p01, 2021)
Tax avoidance is the taxpayers effort to reduce tax payments to the government made by taxpayers, especially companies because they do not violate regulations regarding taxation.   This study aims to examine the effect of corporate social responsibility and free cash flow on tax avoidance which is proxied by using the cash effective tax rate (CETR). This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The sample used was 68 companies with a total observation sample of 272  in 4 years. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of the study show that corporate social responsibility has no effect on tax avoidance and free cash flow has a positive effect on tax avoidance. Keywords: Corporate Social Responsibility; Free Cash Flow; Tax Avoidance.